Inspired by Malaysian batik / Muhammad Nuqman Haqeem Mohd Ramli - Mohd Ramli, Muhammad Nuqman Haqeem (2022)
Malaysian batik is batik textile art in Malaysia, Especially on the east coast of Malaysia. The most popular motifs are leaves and flowers. Malaysian batik depicting humans or animals are rare because Islam norms forbid animal image as decoration.